Analisis Dampak Lingkungan pada Usaha Barang Bekas Perspektif Ekonomi Islam: Studi pada Pengusaha Barang Bekas di Kelurahan Pagar Dewa Kota Bengkulu - Dona Kaita; Romi Adetio Setiawan; Khairiah Elwardah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the environmental impact on used goods business activities in Pagar Dewa Village, Bengkulu City, by referring to Standard Operating Procedures (SOP) and Environmental Impact Analysis (AMDAL) regulations from an Islamic economic perspective. This study specifically uses the maslahah murrasa approach in fiqh rules as the main analytical framework. The research method used is field research with a qualitative approach. The research results show that there are a number of problems related to the responsibility of second-hand goods entrepreneurs towards environmental aspects. Entrepreneurs in the area are known to set up businesses in residential areas, which results in air and environmental pollution. This pollution has a direct impact on the surrounding community, which experiences continuous disturbances in the form of unpleasant odors. Until now, no concrete solution has been found by entrepreneurs to overcome this problem. In a review of Islamic economics, it was found that business actors have not fully complied with Islamic principles regarding environmental management and preservation. Based on the analysis of natural resources and the environment from an Islamic perspective, the Al-Istislah concept and the approach to the basic objectives of Islamic law (Maqasid al-Syari'ah) should be the main guidelines for business actors in maintaining a balance between economic benefits and environmental preservation.